An analysis of the productivity and technical efficiency of smallholder irrigation in Ethiopia - Makombe, Godswill; Namara, Regassa E.; Awulachew, Seleshi Bekele; Hagos, Fitsum; Kanjere, M. (African Journals Online, 2017)
Agriculture is the mainstay of Ethiopia’s economy, contributing more than 40% to GDP and providing a livelihood to about 80% of the population. Agriculture is dominated by smallholders growing predominantly rainfed cereals, making economic performance dependent on rainfall availability. This study used the stochastic frontier production function to analyse the productivity and technical efficiency of 4 different agricultural production systems in Ethiopia; namely, irrigated seasonal farms on traditional irrigation systems, irrigated seasonal farms on modern communal irrigation systems, rainfed seasonal farms for farmers who have access to irrigation and rainfed seasonal farms for farmers who do not have access to irrigation. Simple random samples of farmers were selected from lists of farmers. The sample of farmers constituted 122 from the traditional irrigated sites, 281 from the modern communal irrigated sites and 350 from the control rainfed sites of farmers without access to irrigation. For those farmers, from both traditional and modern communal irrigation, who also had access to rainfed farms, their rainfed farms were included in the sample of rainfed with access to irrigation. This sample constituted 434 farmers. The marginal productivity of land on modern communal irrigation systems shows that this is the smallholder irrigation option that should be developed by the Government of Ethiopia. However, the marginal productivity of land in the ‘rainfed without access to irrigation’ category is higher than that of the traditional irrigated system. Thus additional developed land should be put under ‘rainfed without access to irrigation’ before it is put under traditional irrigation; otherwise it should be developed into modern communal irrigation. The average technical efficiency for the modern irrigated system was estimated to be about 71%, whereas this was estimated to be 78% for the ‘rainfed without access to irrigation’ system. There are potential gains to be realised in improving efficiency in these two systems.